HET 222 Fonetik dan Fonologi September 1997 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 1997)
UNIVERSITI SAINS MALAYSIA Peperiksaan Semester Pertama Sidang Akademik 1997/98 September 1997 HET 222 Fonetik dan Fonologi Masa: [3 jam] THIS EXAMINATION PAPER CONTAINS TEN [10] QUESTIONS IN TWENTY ONE [21] PAGES. Answer ALL TEN [10] questions in both sections. Questions 1. 2, 3, 4, 5 and 6 in Section A are to be answered in these sheets and questions 7, 8, 9 and 10 are to be answered in the answer booklets.